A rapid preparation method and application of a multi-strained ruthenium-based pyrochlore catalyst

Through multi-strain and Joule heat treatment technology, the geometric configuration and electronic structure of the ruthenium-based pyrochlore catalyst are adjusted to solve the problems of long reaction time, high energy consumption and low activity in traditional preparation methods, and achieve efficient acidic OER performance and industrialization Application prospects.

CN118792695BActive Publication Date: 2025-01-21SHANDONG HAIHUA GRP CO LTD
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202411264331.6
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-09-10
Publication Date
2025-01-21
Estimated Expiration
2044-09-10

AI Technical Summary

Technical Problem

During the traditional pyrolysis preparation of ruthenium calcinite catalyst, the reaction time is long, the energy consumption is huge, the geometric configuration and component modulation are poor, and the catalyst activity and stability are low.

Method used

By causing multiple strains, the geometric configuration and electronic structure of Ru in the Ru-based pyrochlore catalyst are adjusted, Joule heat treatment technology and citric acid are used to adjust the pH, and potassium chloride and potassium citrate are combined to form a molten salt to increase porosity and crystal lattice strain.

Benefits of technology

It significantly improves the activity and stability of the catalyst, reduces energy consumption, achieves efficient acidic oxygen evolution reaction (OER) performance, and has broad industrial prospects.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN118792695B_ABST
    Figure CN118792695B_ABST
Patent Text Reader

Abstract

The present invention provides a rapid preparation method and application of a multi-strain ruthenium-based pyrochlore catalyst, which belongs to the field of electrochemical technology. The present invention first forms a gel material through a metal salt complex reaction, then adds a potassium chloride additive and assists with Joule heat treatment technology to prepare a multi-strain ruthenium-based pyrochlore catalyst. This preparation method can inhibit the agglomeration of potassium ions and stabilize the uniform doping of potassium ions in the pyrochlore bulk phase. At the same time, the rapid temperature rise and fall process causes a large temperature difference between the inner and outer layers of the pyrochlore crystal, resulting in non-uniform bulk phase deformation inside and between the crystals, and the local lattice strain caused by potassium ion doping, so that the prepared pyrochlore catalyst has multiple strain characteristics, thereby adjusting the geometric configuration and electronic structure of Ru in the Ru-based pyrochlore catalyst, alleviating the loss of Ru elements in the electrocatalytic process and improving the intrinsic activity of Ru, and showing excellent acidic water electrolysis oxygen evolution performance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a rapid preparation method and application of a multi-strain ruthenium-based pyrochlore catalyst, belonging to the technical field of electrochemistry. Background Art

[0002] The oxygen evolution reaction (OER) plays an important role in both hydrogen production from water electrolysis and power generation from regenerative fuel cells. Current OER catalysts are still constrained by their slow reaction kinetics and instability in acidic media. Compared with alkaline systems, acidic systems have higher ionic conductivity and fewer side reactions, and are generally more suitable for OER reactions. However, acidic OER catalysts are still mainly based on classic RuO2 and IrO2, but their high prices and limited reserves limit their feasibility in large-scale commercial applications. Therefore, it is of great significance to develop an OER catalyst suitable for acidic media.

[0003] Ruthenium-based pyrochlores have become potential alternative materials for oxygen evolution reaction in water electrolysis due to their unique crystal structure and good electrocatalytic performance. Such materials have abundant active sites and excellent electron transport properties, thus showing excellent oxygen evolution efficiency. At present, the conventional preparation methods of ruthenium-based pyrochlores involve high-temperature preparation and long-term heat preservation, which not only consumes a lot of energy, but also limits the further optimization of material properties. In addition, these methods often hinder the designability of the geometric configuration and composition modulation of the materials, further reducing their technical and economic feasibility. Therefore, the development of a fast, low-cost and efficient method for preparing ruthenium-based pyrochlores is not only of great significance for improving the performance of OER catalysts and reducing the cost of water electrolysis, but also has a far-reaching impact on promoting the development and application of renewable energy technologies.

[0004] The Chinese invention patent document with publication number CN115196696A discloses a yttrium ruthenate nanocatalyst, its preparation method and application. The invention obtains a yttrium ruthenate pyrochlore nanocatalyst with a rich defect structure by high-temperature heat treatment combined with a quenching process. This method adopts the traditional pyrolysis method, which requires long-term high-temperature calcination for more than 24 hours in an air atmosphere, and also requires quenching process with 0-20°C water or salt solution and dry ice and liquid nitrogen to obtain a catalyst with rich defects. The preparation efficiency of this catalyst is low, the process is complex, and the energy consumption is high. This method does not involve the regulation of the geometric configuration and electronic structure of the intrinsic active site Ru, and has limited effect on the improvement of the intrinsic activity of the catalyst, that is, at 10mA·cm -2 The overpotential of OER at a current density of 2.5 and an electrolyte of 0.1M HClO4 is 245 mV. In addition, the catalyst prepared by this method was only tested for stability for 10 hours, which is far from the industrial stability time.

[0005] The Chinese invention patent document with the publication number CN115449842A discloses a lead-doped low-temperature synthesized yttrium ruthenate catalyst and its preparation method and application. The invention uses metal salts of ruthenium, yttrium and lead as precursors dissolved in water, adds water-soluble organic matter as fuel, ages to form a gel, and then heat-treats at a relatively low temperature to obtain a lead-doped low-temperature synthesized yttrium ruthenate catalyst. The traditional pyrolysis preparation of pyrochlore structure requires high-temperature heat treatment above 1100°C and a long-term insulation process of 18-72h. This method can form a good pyrochlore structure at a relatively low temperature of 200-950°C and a relatively short time of 2-12h, but it is still difficult to significantly break through the problem of time-consuming and energy-consuming traditional pyrolysis methods. In the embodiment of the method, the calcination temperature is still not less than 400°C, and the insulation time is 8h. Due to the long-term constant temperature and slow temperature rise and fall process, it is easy to cause the agglomeration of doped atoms and the lack of defects, which hinders the controllability of the active site geometry and electronic structure, resulting in reduced performance of the catalyst. Summary of the invention

[0006] The purpose of the present invention is to provide a rapid preparation method of a multi-strained ruthenium-based pyrochlore catalyst, which can solve the problems of long reaction time, huge energy consumption, poor designability of geometric configuration and composition modulation, and low catalyst activity and stability in the traditional pyrolysis catalyst preparation process. The method significantly adjusts the geometric configuration and electronic structure of Ru in the Ru-based pyrochlore catalyst by inducing multiple strains, alleviates the loss of Ru elements in the electrocatalytic process and improves the intrinsic activity of Ru, thereby showing efficient acidic OER performance and having broad industrial prospects.

[0007] To achieve this object, the technical solution of the present invention is:

[0008] A method for rapidly preparing a multi-strained ruthenium-based pyrochlore catalyst comprises the following steps:

[0009] (1) adding yttrium nitrate, ruthenium trichloride and potassium citrate to deionized water and mixing them evenly, then continuously adding citric acid under stirring to adjust the pH value of the solution to 3-5, thereby obtaining a first mixed solution;

[0010] (2) stirring the first mixed solution at 80-95° C. for 5-10 hours to obtain a gel; vacuum drying the gel at 60-100° C. for 10-12 hours to obtain gel solid particles;

[0011] (3) The gel solid particles and potassium chloride are mixed and ground into powder, and then the powder is placed in a groove of a graphite sample stage of a Joule heating device, and then subjected to Joule heat treatment in air or other oxygen-containing atmospheres. After washing and vacuum drying, a multi-strained ruthenium-based pyrochlore catalyst is obtained.

[0012] The inventors found in the experimental process of step (2) that when the reaction temperature is lower than 80°C, no gel can be obtained after stirring the reaction for 10 hours; when the temperature is higher than 95°C, the mixed solution will boil after long-term heating, causing the solution to splash, which is somewhat dangerous. Therefore, the reaction conditions should be properly controlled.

[0013] Furthermore, in step (1), the usage ratio of yttrium nitrate, ruthenium trichloride, potassium citrate and deionized water is 1mmol:1.25-2.0mmol:0.5-1mmol:40-80mL.

[0014] Furthermore, in the step (3), the ratio of the amount of the gel solid particles to the amount of potassium chloride is 1g:5-10g.

[0015] Furthermore, in step (3), the conditions of Joule heat treatment are: heat treatment temperature 800-1500°C, heating rate 1000-4000°C / s, and Joule heat treatment times 4-10 times. Joule heat treatment is heating from room temperature to the target temperature, and then naturally cooling to room temperature, which is represented as one time.

[0016] Furthermore, in step (3), the washing conditions are: washing with deionized water and ethanol three to five times respectively; and the vacuum drying conditions are: drying temperature 50-80°C, drying time 5-10h.

[0017] Another object of the present invention is to provide an application of a multi-strained ruthenium-based pyrochlore catalyst prepared by the above method, which is used as an electrochemical catalyst in oxygen evolution reaction (OER) under acidic conditions.

[0018] The beneficial effects of the present invention are:

[0019] (1) Compared with the traditional tubular furnace or muffle furnace calcination method, the Joule heat treatment technology of the present invention has simple equipment operation, high catalyst preparation efficiency, and low energy consumption. It helps to inhibit the collapse of the pore structure and the agglomeration of metal atoms at high temperatures, while ensuring that the catalyst has high activity and stability.

[0020] (2) The citric acid of the present invention helps to adjust the pH of the solution, shortens the reaction time, reduces the addition of potassium citrate, increases the gel formation rate, and reduces the process operation cost.

[0021] (3) The present invention uses potassium chloride and residual potassium citrate as additives to form molten salts during a high-temperature process, and releases a large amount of CO2 during the pyrolysis process, thereby generating a local extreme environment of high temperature and high pressure, which increases the porosity of the multi-strained ruthenium-based pyrochlore catalyst; at the same time, potassium ions will be uniformly doped into the pyrochlore bulk phase during the high-temperature calcination process, causing a contraction effect of the local lattice on the catalyst crystal surface. In addition, the rapid heating and cooling characteristics of the Joule heat treatment technology will cause a large temperature difference between the inner and outer layers of the pyrochlore crystal, and will also cause non-uniform bulk phase deformation inside and between the crystals, thereby synergizing the local lattice strain caused by potassium ion doping, so that the prepared pyrochlore catalyst has multi-strain characteristics. Multi-strain significantly regulates the geometric configuration and electronic structure of Ru in the Ru-based pyrochlore catalyst, alleviates the loss of Ru elements during the electrocatalytic process and improves the intrinsic activity of Ru, and has a synergistic effect with the multi-level pore structure of the multi-strained ruthenium-based pyrochlore catalyst, thereby showing excellent oxygen evolution performance in water electrolysis.

[0022] (4) The multi-strained ruthenium-based pyrochlore catalyst of the present invention has outstanding performance in oxygen evolution reaction under acidic conditions, and its pore size range is 3-65nm, belonging to a multi-level pore structure. -2 Under the current density, the OER overpotential and stability time of the catalyst are 190.5-220.6 mV and 48-50 h respectively, which are much lower than the 310.6 mV overpotential of commercial RuO2 under the same conditions, and the industrialization prospects are broad. BRIEF DESCRIPTION OF THE DRAWINGS

[0023] Figure 1 The high-resolution transmission electron microscopy test of the multi-strained ruthenium-based pyrochlore catalyst obtained in step (3) of Example 1 is shown in FIG. Figure 1 (a) is a low-magnification transmission electron microscope. Figure 1 (b) and (c) are high-magnification transmission electron microscopy images of different areas;

[0024] Figure 2 is an X-ray diffraction (XRD) pattern of the multi-strained ruthenium-based pyrochlore catalyst obtained in step (3) of Example 1;

[0025] Figure 3 The linear sweep voltammetry (LSV) test graph of the oxygen evolution reaction of the multi-strained ruthenium-based pyrochlore catalyst obtained in step (3) of Example 1;

[0026] Figure 4 This is a stability test diagram of the oxygen evolution reaction of the multi-strained ruthenium-based pyrochlore catalyst obtained in step (3) of Example 1. DETAILED DESCRIPTION

[0027] The present invention is further described below in conjunction with the accompanying drawings and specific embodiments so that a person skilled in the art can better understand and implement the present invention, but the protection scope of the present invention is not limited thereto.

[0028] Unless otherwise specified, the raw materials used in the embodiments of the present invention are all commercially available materials; unless otherwise specified, all technical and scientific terms used in the present invention have the same meanings as those generally understood by those skilled in the art.

[0029] In a specific embodiment of the present invention, the Joule heating device used is composed of a gas circuit device, a vacuum pump, a graphite sample stage, a temperature control system, and a data acquisition system. The model is CIS-JH3.3-P, the output voltage is 0-40V, the output current is 0-500A, the temperature measurement range is 0-3000℃, the power supply is 380V / 30A, and the current ramp time is 1ms. Example 1

[0030] (1) adding 1 mmol of yttrium nitrate, 1.5 mmol of ruthenium trichloride, and 0.75 mmol of potassium citrate to 60 mL of deionized water and mixing them evenly, then adding citric acid under stirring to adjust the pH of the solution to 3, thereby obtaining a first mixed solution;

[0031] (2) stirring the first mixed solution at 90° C. for 8 h to obtain a gel; vacuum drying the gel at 80° C. for 11 h to obtain gel solid particles;

[0032] (3) 1 g of gel solid particles and 8 g of potassium chloride were mixed and ground into powder, and then 0.2 g of the powder was placed in the groove of the graphite sample stage of the Joule heating device, and then Joule heat treatment was performed 6 times in an air atmosphere, the Joule heat treatment temperature was 1200°C, and the Joule heat treatment heating rate was 2000°C / s. The mixture was washed with deionized water and ethanol four times respectively, and vacuum dried at 65°C for 8 hours to obtain a multi-strained ruthenium-based pyrochlore catalyst. In addition, in this embodiment, the powder was subjected to Joule heat treatment in an air atmosphere, and Joule heat treatment in other oxygen-containing atmospheres can also achieve the purpose of the invention.

[0033] The multi-strained ruthenium-based pyrochlore catalyst obtained in step (3) was subjected to high-resolution transmission electron microscopy test, X-ray diffraction (XRD) test, and nitrogen total adsorption (N2-BET) pore size distribution test, respectively. Figure 1 , Figure 2 , Table 1. Among them, Figure 1 include: Figure 1 (a) Low-magnification transmission electron microscopy, Figure 1 (b) and (c) are high-magnification transmission electron microscopy images of different areas; the pore size distribution test results of N2-BET in Table 1 are the full-pore pore size distribution based on the NLDFT model.

[0034] Depend on Figure 1 As shown in (a), the multi-strained ruthenium-based pyrochlore catalyst is mainly composed of nanoparticles that are tightly bonded and stacked together; Figure 1 (b) It can be seen that the lattice fringe spacing of the multi-strained ruthenium-based pyrochlore catalyst is 0.284nm, corresponding to the (222) crystal plane of pyrochlore. This lattice spacing is significantly lower than the spacing of the (222) crystal plane of the standard pyrochlore Y2Ru2O7 (0.292nm). The main reason for the difference is that K ions with a smaller radius are doped into the pyrochlore structure, causing the local lattice of the (222) crystal plane of the catalyst to shrink; Figure 1 (c) It can be seen that the (222) crystal plane of the multi-strained ruthenium-based pyrochlore catalyst has different degrees of contraction, expansion and distortion. These phenomena are mainly caused by the uneven bulk phase deformation inside the crystal. The source of this bulk phase deformation is the temperature difference between the inner and outer layers of the pyrochlore crystal during the rapid temperature change. As shown in Table 1, the pore size range of the multi-strained ruthenium-based pyrochlore catalyst is 3-65nm, which belongs to the multi-level pore structure of mesopores and macropores. The porous structure is conducive to the desorption of product oxygen, which has a synergistic effect with the strain of the multi-strained ruthenium-based pyrochlore catalyst and jointly improves the OER performance under acidic conditions.

[0035] The multi-strained ruthenium-based pyrochlore catalyst obtained in step (3) is used for electrocatalytic oxygen evolution reaction (OER) application, comprising the following application steps:

[0036] 4 mg of multi-strained ruthenium-based pyrochlore catalyst and 1 mg of commercial carbon black were dispersed in 0.5 mL of ethanol-Nafion mixed solution (mixed with 0.48 mL of ethanol and 0.02 mL of 0.5% Nafion solution). After ultrasonic treatment for 2 hours, a uniformly dispersed multi-strained ruthenium-based pyrochlore catalyst mixed solution was obtained; 10 uL of the multi-strained ruthenium-based pyrochlore catalyst mixed solution was dripped on the glassy carbon electrode, and after natural air drying, a glassy carbon electrode modified with a multi-strained ruthenium-based pyrochlore catalyst was obtained. The electrochemical test was carried out on a CHI760E electrochemical workstation, using a glassy carbon electrode modified with a multi-strained ruthenium-based pyrochlore catalyst as the working electrode, a graphite rod as the counter electrode, saturated calomel as the reference electrode, and a 0.1M HClO4 aqueous solution as the electrolyte. The linear sweep voltammetry (LSV) test and stability test of the oxygen evolution reaction were carried out, and the test results are shown in Figure 2. Figure 3 , Figure 4 .

[0037] Depend on Figure 3 It can be seen that at 10 mA cm -2 At a current density of 1.3 Å, the glassy carbon electrode modified with the multi-strained ruthenium-based pyrochlore catalyst only requires an overpotential of 190.5 mV, which is much lower than that of commercial RuO2 (310.6 mV@10 mA·cm-2 ), has broad prospects for industrial application.

[0038] Depend on Figure 4 It can be seen that at 10 mA cm -2 After testing for 50 h at a current density of , the overpotential hardly increased, indicating that the glassy carbon electrode modified with the multi-strained ruthenium-based pyrochlore catalyst has excellent stability. Example 2

[0039] (1) adding 1 mmol of yttrium nitrate, 1.25 mmol of ruthenium trichloride, and 0.5 mmol of potassium citrate to 40 mL of deionized water and mixing them evenly, then adding citric acid under stirring to adjust the pH of the solution to 4, thereby obtaining a first mixed solution;

[0040] (2) stirring the first mixed solution at 80° C. for 10 h to obtain a gel; vacuum drying the gel at 60° C. for 12 h to obtain gel solid particles;

[0041] (3) 1 g of gel solid particles and 5 g of potassium chloride were mixed and ground into powder. Then, 0.2 g of the powder was placed in the groove of the graphite sample stage of a Joule heating device. The mixture was subjected to Joule heat treatment 10 times in an air atmosphere at a Joule heat treatment temperature of 800 °C and a Joule heat treatment heating rate of 4000 °C / s. The mixture was washed three times with deionized water and ethanol respectively, and vacuum dried at 50 °C for 10 h to obtain a multi-strained ruthenium-based pyrochlore catalyst.

[0042] The multi-strained ruthenium-based pyrochlore catalyst obtained in step (3) was subjected to N2-BET pore size distribution test. The test results are shown in Table 1.

[0043] As shown in Table 1, the pore size range of the multi-strained ruthenium-based pyrochlore catalyst is 2-60 nm, which belongs to a multi-level pore structure of micropores, mesopores and macropores. The porous structure is conducive to the desorption of product oxygen, and has a synergistic effect with the strain of the multi-strained ruthenium-based pyrochlore catalyst, jointly improving the OER performance under acidic conditions.

[0044] The multi-strained ruthenium-based pyrochlore catalyst obtained in step (3) was used for electrocatalytic OER applications. The test steps and test methods were the same as those in Example 1. The test results are shown in Table 1.

[0045] From Table 1, we can see that at 10 mA cm -2 At a current density of 1.3 Å, the glassy carbon electrode modified with the multi-strained ruthenium-based pyrochlore catalyst only requires an overpotential of 220.6 mV, which is much lower than that of commercial RuO2 (310.6 mV@10 mA·cm -2 ), has broad prospects for industrial application; at 10mA·cm -2After testing for 48 h at a current density of , the overpotential began to change, indicating that the glassy carbon electrode modified with the multi-strained ruthenium-based pyrochlore catalyst has excellent stability. Example 3

[0046] (1) adding 1 mmol of yttrium nitrate, 2.0 mmol of ruthenium trichloride, and 1.0 mmol of potassium citrate to 80 mL of deionized water and mixing them evenly, then adding citric acid under stirring and adjusting the pH of the solution to 5 to obtain a first mixed solution;

[0047] (2) stirring the first mixed solution at 95° C. for 5 h to obtain a gel; vacuum drying the gel at 100° C. for 10 h to obtain gel solid particles;

[0048] (3) 1 g of gel solid particles and 10 g of potassium chloride were mixed and ground into powder. Then, 0.2 g of the powder was placed in the groove of the graphite sample stage of a Joule heating device. The mixture was subjected to Joule heat treatment four times in an air atmosphere at a Joule heat treatment temperature of 1500°C and a Joule heat treatment heating rate of 1000°C / s. The mixture was washed with deionized water and ethanol five times respectively and vacuum dried at 80°C for 5 h to obtain a multi-strained ruthenium-based pyrochlore catalyst.

[0049] The multi-strained ruthenium-based pyrochlore catalyst obtained in step (3) was subjected to N2-BET pore size distribution test. The test results are shown in Table 1.

[0050] As shown in Table 1, the pore size range of the multi-strained ruthenium-based pyrochlore catalyst is 3-62 nm, which belongs to a multi-level pore structure of mesopores and macropores. The porous structure is conducive to the desorption of product oxygen, and has a synergistic effect with the strain of the multi-strained ruthenium-based pyrochlore catalyst, jointly improving the OER performance under acidic conditions.

[0051] The multi-strained ruthenium-based pyrochlore catalyst obtained in step (3) was used for electrocatalytic OER applications. The test steps and test methods were the same as those in Example 1. The test results are shown in Table 1.

[0052] From Table 1, we can see that at 10 mA cm -2 At a current density of 1.3 Å, the glassy carbon electrode modified with the multi-strained ruthenium-based pyrochlore catalyst only requires an overpotential of 200.7 mV, which is much lower than that of commercial RuO2 (310.6 mV@10 mA·cm -2 ), has broad prospects for industrial application; at 10mA·cm -2 After testing for 49 h at a current density of , the overpotential began to change, indicating that the glassy carbon electrode modified with the multi-strained ruthenium-based pyrochlore catalyst has excellent stability. Example 4

[0053] (1) adding 1 mmol of yttrium nitrate, 1.4 mmol of ruthenium trichloride, and 0.70 mmol of potassium citrate to 70 mL of deionized water and mixing them evenly, then adding citric acid under stirring to adjust the pH of the solution to 3.5 to obtain a first mixed solution;

[0054] (2) stirring the first mixed solution at 85° C. for 8 h to obtain a gel; vacuum drying the gel at 80° C. for 12 h to obtain gel solid particles;

[0055] (3) 1 g of gel solid particles and 8 g of potassium chloride were mixed and ground into powder. Then, 0.2 g of the powder was placed in the groove of the graphite sample stage of a Joule heating device. The mixture was subjected to Joule heat treatment for 6 times in an air atmosphere at a Joule heat treatment temperature of 1200°C and a Joule heat treatment heating rate of 1500°C / s. The mixture was washed four times with deionized water and ethanol respectively, and vacuum dried at 75°C for 8 h to obtain a multi-strained ruthenium-based pyrochlore catalyst.

[0056] The multi-strained ruthenium-based pyrochlore catalyst obtained in step (3) was subjected to N2-BET pore size distribution test. The test results are shown in Table 1.

[0057] As can be seen from Table 1, the pore size range of the multi-strained ruthenium-based pyrochlore catalyst is 3-64 nm, which belongs to a multi-level pore structure of mesopores and macropores. The porous structure is conducive to the desorption of product oxygen, and has a synergistic effect with the strain of the multi-strained ruthenium-based pyrochlore catalyst, jointly improving the OER performance under acidic conditions.

[0058] The multi-strained ruthenium-based pyrochlore catalyst obtained in step (3) was used for electrocatalytic OER applications. The test steps and test methods were the same as those in Example 1. The test results are shown in Table 1.

[0059] From Table 1, we can see that at 10 mA cm -2 At a current density of 1.3 Å, the glassy carbon electrode modified with the multi-strained ruthenium-based pyrochlore catalyst only requires an overpotential of 192.6 mV, which is much lower than that of commercial RuO2 (310.6 mV@10 mA·cm -2 ), has broad prospects for industrial application; at 10mA·cm -2 After testing for 50 h at a current density of , the overpotential began to change, indicating that the glassy carbon electrode modified with the multi-strained ruthenium-based pyrochlore catalyst has excellent stability. Comparative Example 1

[0060] The difference between Comparative Example 1 and Example 1 is that the heating device in step (3) is different, the Joule heating device is replaced with a tube furnace, and the other steps remain unchanged. The specific operation is as follows:

[0061] 1 g of gel solid particles and 5 g (8 g in Example 1) of potassium chloride were mixed and ground into powder, and then 0.2 g of the powder was placed in a tubular furnace and calcined in an oxygen-containing atmosphere of air at a calcination temperature of 1200°C and a heating rate of 10°C / min. The reaction was kept warm for 2 hours to obtain a pyrochlore catalyst.

[0062] The pyrochlore catalyst was subjected to N2-BET pore size distribution test, and the test results are shown in Table 1.

[0063] It can be seen from Table 1 that the pore size range of the pyrochlore catalyst is 3-45 nm, which is much lower than the pore size range of Example 1. Therefore, it can be seen that calcination in a tubular furnace will lead to the collapse of the pores.

[0064] The pyrochlore catalyst was subjected to electrocatalytic OER application. The test steps and test methods were the same as those in Example 1. The test results are shown in Table 1.

[0065] As shown in Table 1, in 0.1M HClO4 electrolyte and 10mA·cm -2 The OER overpotential of the glassy carbon electrode modified with the pyrochlore catalyst at a current density of 340.6 mV is much higher than that of the glassy carbon electrode modified with the multi-strained ruthenium-based pyrochlore catalyst prepared in Example 1 (190.5 mV@10 mA·cm -2 ) and commercial RuO2 (310.6 mV@10 mA·cm -2 ) catalytic activity, and high energy consumption; the stabilization time of the glassy carbon electrode modified with pyrochlore catalyst is 20h, which is much shorter than the stabilization time of Example 1. This is mainly because the calcination in the traditional tube furnace cannot provide instantaneous high temperature and cannot generate lattice stress in the catalyst; secondly, the calcination in the traditional tube furnace will cause the agglomeration of metal atoms in the catalyst, and the combined effect of the two leads to poor catalytic performance. Comparative Example 2

[0066] The difference between Comparative Example 2 and Example 1 is that potassium chloride is not added in step (3), and the other steps remain unchanged.

[0067] The pyrochlore catalyst obtained in step (3) was subjected to N2-BET pore size distribution test. The test results are shown in Table 1.

[0068] As can be seen from Table 1, the pore size range of the pyrochlore catalyst is 3-55 nm, which belongs to a multi-level pore structure of mesopores and macropores, but is far lower than the pore size range of Example 1. This is mainly because without the addition of potassium chloride, molten salt cannot be formed at high temperature, no large amount of CO2 is generated, and the high-pressure environment inside the catalyst cannot be obtained, which leads to a smaller pore size.

[0069] The pyrochlore catalyst obtained in step (3) was used for electrocatalytic OER application. The test steps and test methods were the same as those in Example 1. The test results are shown in Table 1.

[0070] From Table 1, we can see that at 10 mA cm -2 At a current density of 1.3 Å, the pyrochlore catalyst-modified glassy carbon electrode only requires an overpotential of 325.8 mV, which is much higher than that of commercial RuO2 (310.6 mV@10 mA cm -2 ) and Example 1 (190.5 mV@10 mA·cm -2 ) catalytic activity. In addition, at 10 mA cm -2 After 38 hours of testing at a current density of , the overpotential began to change, which was much shorter than the stabilization time of Example 1. This was mainly because there was no addition of potassium chloride, resulting in less or no potassium ion doping, no shrinkage effect of the local lattice of the crystal face or a poor lattice shrinkage effect, which reduced the synergistic effect of the volume phase deformation caused by the rapid heating and cooling characteristics of the Joule heat treatment technology, and thus less strain on the catalyst, thereby reducing the catalytic activity. Comparative Example 3

[0071] The difference between Comparative Example 3 and Example 1 is that potassium citrate is not added in step (1), and the other steps remain unchanged.

[0072] The pyrochlore catalyst obtained in step (3) was subjected to N2-BET pore size distribution test. The test results are shown in Table 1.

[0073] As can be seen from Table 1, the pore size range of the pyrochlore catalyst is 3-50 nm, which belongs to a multi-level pore structure of mesopores and macropores, but is far lower than the pore size range of Example 1. This is mainly because without the addition of potassium citrate, molten salt cannot be formed at high temperature, no large amount of CO2 is generated, and the high pressure environment inside the catalyst cannot be obtained, which leads to a smaller pore size.

[0074] The pyrochlore catalyst obtained in step (3) was used for electrocatalytic OER application. The test steps and test methods were the same as those in Example 1. The test results are shown in Table 1.

[0075] From Table 1, we can see that at 10 mA cm -2 At a current density of 1.3 Å, the pyrochlore catalyst-modified glassy carbon electrode only requires an overpotential of 335.7 mV, which is much higher than that of commercial RuO2 (310.6 mV@10 mA cm -2 ) and Example 1 (190.5 mV@10 mA·cm -2 ) catalytic activity. In addition, at 10 mA cm -2After testing for 36 hours at a current density of , the overpotential began to change, which was much lower than the stabilization time of Example 1. This is mainly because without the addition of potassium citrate, potassium ion doping is less, the shrinkage effect of the local lattice of the crystal surface is smaller, and the synergistic effect of the catalyst body corresponding to the Joule heat treatment technology due to the rapid temperature rise and fall characteristics is reduced, and then the strain of the catalyst is less, thereby reducing the catalytic activity. Therefore, combined with Comparative Example 3, it can be seen that the addition of potassium citrate and potassium chloride has an important influence. Comparative Example 4

[0076] The difference between Comparative Example 4 and Example 1 is that no citric acid is added in step (1). The operation steps are as follows:

[0077] (1) Add 1 mmol of yttrium nitrate, 1.5 mmol of ruthenium trichloride, and 0.75 mmol of potassium citrate to 60 mL of deionized water, and stir to mix well to obtain a first mixed solution;

[0078] (2) The first mixed solution was stirred and reacted at 90° C. for 24 hours to obtain a gel; the gel was vacuum dried at 80° C. for 11 hours to obtain gel solid particles.

[0079] During the experiment, we found that when citric acid was not added, the gel state could not be obtained at a reaction time of 8 hours. The gel could only be obtained when the reaction time was extended to 24 hours. Therefore, the addition of citric acid helps to accelerate the formation of gel, reduce the reaction time, reduce the process operation time, and also reduce the amount of potassium citrate added, thereby reducing the cost. It can be seen that citric acid is a beneficial supplement to potassium citrate and can reduce the process operation cost. Comparative Example 5

[0080] The difference between Comparative Example 5 and Example 1 is that a washing operation is added in step (2), and the other steps remain unchanged. The operation steps are as follows:

[0081] The first mixed solution is stirred and reacted at 90°C for 24 hours (8 hours in Example 1) to obtain a gel; the gel is vacuum dried at 80°C for 11 hours to obtain gel solid particles; the gel solid particles are washed four times with deionized water and ethanol, and vacuum dried at 80°C for 10 hours to obtain cleaned gel solid particles.

[0082] The pyrochlore catalyst obtained in step (3) was used for electrocatalytic OER application. The test steps and test methods were the same as those in Example 1. The test results are shown in Table 1.

[0083] From Table 1, we can see that at 10 mA cm -2 At a current density of 1.3 Å, the pyrochlore catalyst-modified glassy carbon electrode only requires an overpotential of 320.8 mV, which is much higher than that of commercial RuO2 (310.6 mV@10 mA cm-2 ) and Example 1 (190.5 mV@10 mA·cm -2 ) catalytic activity. In addition, at 10 mA cm -2 After 38 hours of testing at a current density of , the overpotential began to change, which was much lower than the stabilization time of Example 1. This is mainly because the residual potassium citrate in the catalyst will be washed away during the washing process, resulting in less potassium ion doping, less shrinkage effect of the local lattice on the crystal surface, and reduced synergistic effect with the Joule heat treatment technology due to the rapid temperature rise and fall characteristics to produce volume phase changes, and thus less strain on the catalyst, thereby reducing the catalytic activity. Therefore, the no-washing operation step is very important.

[0084]

[0085] From the above, it can be seen that the performance of the catalyst prepared by the traditional tubular furnace calcination method is significantly inferior to that of the catalyst prepared by the Joule heat treatment technology. The main reason is that the heating and cooling speeds of the traditional calcination process are relatively slow, which easily leads to sintering of the catalyst and collapse of the pores, making it difficult to form defects and lattice strains and a wider multi-level pore structure. This sintering will hinder the transfer of substances and block the active sites on the catalyst surface, thereby affecting the catalytic efficiency of OER. Joule heat treatment technology is a key influencing factor in obtaining multi-strain ruthenium-based pyrochlore catalysts. Potassium chloride and residual potassium citrate form molten salts at high temperatures and release a large amount of CO2 during pyrolysis, thereby generating a local extreme environment of high temperature and pressure, which increases the porosity of the multi-strained ruthenium-based pyrochlore catalyst. At the same time, potassium ions will be doped into the pyrochlore bulk phase during high-temperature calcination, causing the contraction of the local lattice of the catalyst crystal surface, which has a synergistic effect with the bulk phase transformation of the catalyst caused by the Joule heat treatment technology due to the rapid heating and cooling characteristics, thereby preparing a ruthenium-based pyrochlore catalyst with multiple strains, effectively adjusting the geometric structure and electronic structure of the Ru active site in the pyrochlore, thereby significantly improving the acidic OER catalytic performance. Potassium chloride and potassium citrate have the effect of synergistically creating a multi-level pore structure and lattice strain. Citric acid is a favorable supplement to potassium citrate, which can reduce the process operation cost and accelerate the reaction rate. In addition, the gel solid particles cannot be washed, and the washing operation will wash away the excess potassium citrate. Therefore, no washing operation is one of the keys to obtaining a multi-strained ruthenium-based pyrochlore catalyst.

[0086] The above embodiments are intended to illustrate the essential content of the present invention, but are not intended to limit the protection scope of the present invention. Those skilled in the art should understand that the technical solution of the present invention can be modified or replaced by equivalents without departing from the essence and protection scope of the technical solution of the present invention.

Claims

1. A method for rapidly preparing a multi-strained ruthenium-based pyrochlore catalyst, characterized in that: The following steps are involved: (1) adding yttrium nitrate, ruthenium trichloride and potassium citrate to deionized water and mixing them evenly, then continuously adding citric acid under stirring to adjust the pH value of the solution to 3-5, thereby obtaining a first mixed solution; (2) stirring the first mixed solution at 80-95° C. for 5-10 hours to obtain a gel; vacuum drying the gel at 60-100° C. for 10-12 hours to obtain gel solid particles; (3) mixing the gel solid particles and potassium chloride and grinding them into powder, then placing the powder in a groove of a graphite sample stage of a Joule heating device, performing Joule heat treatment under an air atmosphere, washing, and vacuum drying to obtain a multi-strained ruthenium-based pyrochlore catalyst; In the step (3), the conditions of the Joule heat treatment are: heat treatment temperature 800-1500°C, heating rate 1000-4000°C / s, and Joule heat treatment times 4-10 times.

2. The rapid preparation method of the multi-strained ruthenium-based pyrochlore catalyst according to claim 1, characterized in that: In the step (1), the usage ratio of yttrium nitrate, ruthenium trichloride, potassium citrate and deionized water is: 1mmol:1.25-2.0mmol:0.5-1mmol:40-80mL.

3. The rapid preparation method of the multi-strained ruthenium-based pyrochlore catalyst according to claim 1, characterized in that: In the step (3), the ratio of the amount of gel solid particles to potassium chloride is 1g:5-10g.

4. The rapid preparation method of the multi-strained ruthenium-based pyrochlore catalyst according to claim 1, characterized in that: In the step (3), the washing conditions are: washing with deionized water and ethanol three to five times respectively; the vacuum drying conditions are: drying temperature 50-80°C, drying time 5-10h.

5. Use of a multi-strained ruthenium-based pyrochlore catalyst prepared by the preparation method according to any one of claims 1 to 4, characterized in that: It was used as an electrochemical catalyst for oxygen evolution reaction under acidic conditions.

Citation Information

Patent Citations

  • Yttrium ruthenate nano-catalyst as well as preparation method and application thereof

    CN115196696A

  • Lead-doped low-temperature synthesized yttrium ruthenate catalyst as well as preparation method and application thereof

    CN115449842A

  • Sulfur-doped ruthenium acid yttrium, preparation method thereof and oxygen evolution reaction electrode

    CN115652357A

  • Ruthenium-molybdenum alloy composite defect type molybdenum oxide electrocatalyst and preparation method and application thereof

    CN117822037A